Single‐cell/nanoparticle trajectories reveal two‐tier Lévy‐like interactions across bacterial swarms. Issue 6 (3rd November 2022) - Sang, Yuqian; Wen, Xiaodong; He, Yan
Abstract: Swarming bacteria can organize themselves into different local communities, ranging from active cell rafts to reticular biofilms. How millions of motile and immotile cells are dynamically linked together and still function as a whole is a critical interdisciplinary issue. Besides biochemical and molecular characterizations, concerns on the microscopic communication mechanisms underlying the complicated microsystem have been largely simplified to biophysics or physical interactions between individual isolated bacteria. Herein, by single‐cell tracking of fluorescent bacteria in the motile cell layer and single‐particle tracking of gold nanoparticles (AuNPs) in the upper fluid layer in different regions across a swarming colony of Bacillus subtilis, we studied collective multibacteria interactions, using the upper fluid as the medium, in detail. While the dynamic properties differ spatially, both cell migrations and AuNP transports in the swarming edge, the intermediate and the biofilm‐like center regions of the colony can be described with the Lévy‐walk‐like superdiffusion model. Moreover, the speed and motion range of the AuNPs are always much smaller than the bacteria, indicating that the intercellular fluid flow alone cannot explain long‐range cell‐to‐cell signaling. Referring to previous literature, we propose the presence of a decentralized two‐tier "active‐mixing" network in the bacterial community for efficient information exchange. Abstract : Bacterial community is a typical model system to study the behavior of multicellular organization, how millions of cells are organized, and how they communicate efficiently microscopically on large spatiotemporal scales have attracted a lot of attention. By single‐cell tracking of fluorescent bacteria in the motile cell layer and single‐particle tracking of gold nanoparticles (AuNPs) in the upper fluid layer in different regions across a swarming colony of Bacillus subtilis, we studied collective multibacteria interactions, using the upper fluid as the medium, in detail. And we propose a novel "active‐mixing" signal‐transport mechanism, which may provide an efficient and robust active transport network for long‐range cell‐cell communication.